Goal problems in gambling theory - Theodore Hill (Revista de Matemática: Teoría y Aplicaciones, 2009)
A short introduction to goal problems in abstract gambling theory is given, along with statementes of some of the main theorems and a number of examples, open problems and references. Emphasis is on the finite-state, countably-additive setting with such classical objectives as reaching a goal, hitting a goal  infinitely often, staying in the goal, and maximizing the average time spent at a goal.